Substantial Heritable Variation in Recombination Rate on Multiple Scales in Honeybees and Bumblebees. Issue 4 (31st May 2019) - Kawakami, Takeshi; Wallberg, Andreas; Olsson, Anna; Wintermantel, Dimitry; de Miranda, Joachim R; Allsopp, Mike; Rundlöf, Maj; Webster, Matthew T
Abstract: Meiotic recombination shuffles genetic variation and promotes correct segregation of chromosomes. Rates of recombination vary on several scales, both within genomes and between individuals, and this variation is affected by both genetic and environmental factors. Social insects have extremely high rates of recombination, although the evolutionary causes of this are not known. Here, we estimate rates of crossovers and gene conversions in 22 colonies of the honeybee, Apis mellifera, and 9 colonies of the bumblebee, Bombus terrestris, using direct sequencing of 299 haploid drone offspring. We confirm that both species have extremely elevated crossover rates, with higher rates measured in the highly eusocial honeybee than the primitively social bumblebee. There are also significant differences in recombination rate between subspecies of honeybee. There is substantial variation in genome-wide recombination rate between individuals of both A. mellifera and B. terrestris and the distribution of these rates overlap between species. A large proportion of interindividual variation in recombination rate is heritable, which indicates the presence of variation in trans -acting factors that influence recombination genome-wide. We infer that levels of crossover interference are significantly lower in honeybees compared to bumblebees, which may be one mechanism that contributes to higher recombination rates in honeybees. We also find a significant increase in recombination rate with distance from the centromere, mirrored by methylation differences. We detect a strong transmission bias due to GC-biased gene conversion associated with noncrossover gene conversions. Our results shed light on the mechanistic causes of extreme rates of recombination in social insects and the genetic architecture of recombination rate variation.